Increased Collagen Crosslinking in Stiff Clubfoot Tissue: Implications for the Improvement of Therapeutic Strategies - Knitlova, Jarmila; Doubkova, Martina; Eckhardt, Adam; Ostadal, Martin; Musilkova, Jana; Bacakova, Lucie; Novotný, Tomáš (International journal of molecular sciences, 2021)
Congenital clubfoot is a complex musculoskeletal deformity, in which a stiff, contracted tissue forms in the medial part of the foot. Fibrotic changes are associated with increased collagen deposition and lysyl oxidase (LOX)-mediated crosslinking, which impair collagen degradation and increase the tissue stiffness. First, we studied collagen deposition, as well as the expression of collagen and the amount of pyridinoline and deoxypyridinoline crosslinks in the tissue of relapsed clubfoot by immunohistochemistry, real-time PCR, and enzyme-linked immunosorbent assay (ELISA). We then isolated fibroblast-like cells from the contracted tissue to study the potential inhibition of these processes in vitro. We assessed the effects of a LOX inhibitor, β-aminopropionitrile (BAPN), on the cells by a hydroxyproline assay, ELISA, and Second Harmonic Generation imaging. We also evaluated the cell-mediated contraction of extracellular matrix in 3D cell-populated collagen gels. For the first time, we have confirmed significantly increased crosslinking and excessive collagen type I deposition in the clubfoot-contracted tissue. We successfully reduced these processes in vitro in a dose-dependent manner with 10-40 μg/mL of BAPN, and we observed an increasing trend in the inhibition of the cell-mediated contraction of collagen gels. The in vitro inhibitory effects indicate that BAPN has good potential for the treatment of relapsed and resistant clubfeet.
Keywords: Protein-Lysine 6-Oxidase; Cross-Linking Reagents; Humans; lysyloxidasa; Female; lidé; kolagen; reagencia zkříženě vázaná; Collagen; aminopropionitril; předškolní dítě; Clubfoot; ženské pohlaví; Male; pes equinovarus; Aminopropionitrile; fibroblasty; mužské pohlaví; Child, Preschool; Fibroblasts